2011
DOI: 10.1007/s12647-011-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of Coriolis flow meters for low Reynolds number flows

Abstract: In process industries Coriolis mass flow meters (CMFs) are widely employed for measuring mass flows. Quite often, especially in the oil and gas (O&G) industry, owing to fluids with high viscosities, flow measurements may lie in low Reynolds number regions. At low Reynolds numbers (Re), a CMF reading may deviate under the influence of fluid-dynamic forces. With the help of extensive Fluid-Structure-Interaction simulations (FSI), a detailed insight into physical mechanisms leading to this deviation is provided. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 5 publications
3
15
0
3
Order By: Relevance
“…It is known that fluid with different viscosity may have different damping factor (Kumar and Anklin 2011). When the oscillation of the structure domain experience damping during fluid flow, the driver have to excite additional force to compensate for the amplitude loss caused by the fluid's damping.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that fluid with different viscosity may have different damping factor (Kumar and Anklin 2011). When the oscillation of the structure domain experience damping during fluid flow, the driver have to excite additional force to compensate for the amplitude loss caused by the fluid's damping.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement deviation at low Re has significant importance in the metering of highly viscous fluids. Several laboratory and field measurements with certain devices clearly indicate that there can be a shift in the meter calibration factor at viscous liquid (Henry, Tombs et al 2006, Kumar andAnklin 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the fluid viscosity increases there can be increase in the mean velocity in the proportion such that the flow still remains laminar. The performance of CMFM is found to be deviated in this flow regime leading to underestimation of the flow rate as reported by Kumar and Anklin [1]. Bobovnik et al [2] carried out numerical simulations to predict the performance of shell type Coriolis flow meter for a range of Re with the tube of two different aspect ratios.…”
Section: Introductionmentioning
confidence: 78%
“…It was found that at low Reynolds numbers the oscillating viscous fluid forces become relatively strong and interact with the oscillating Coriolis force, which changes the measurement results. To further investigate the effect of the Reynolds numbers, Kumar and Anklin [12] investigated a curved double tube CMF with an FSI simulation. The meter deviation at low Reynolds numbers were found in good agreement to measurement data.…”
Section: Introductionmentioning
confidence: 99%